IMPLEMENTASI PENCATATAN KEUANGAN DIGITAL SEBAGAI UPAYA MENINGKATKAN AKUNTABILITAS UMKM KULINER DI MANADO - Raykes Tuerah; Andreuw K. Pantow; Christony Maradesa; Yelly Paendong; Lidya A Maramis; Fanesa I. M. Syaefudin; Wenny A. Ginting; Sintia N. Korompis; Olifia Y. Tala Tala (LPPM STAI Muhammadiyah Probolinggo, 2026)
Culinary Micro, Small, and Medium Enterprises (MSMEs) in Manado City play an important role in supporting local economic growth. However, many business actors still face challenges in financial management, particularly in transaction recording, which is often conducted manually and lacks proper structure. This condition results in low accuracy of financial information and limited ability to evaluate business performance. This community service program aims to strengthen the financial governance of culinary MSMEs through the implementation of digital financial recording using the Si Apik application and Microsoft Excel. The program employed a descriptive qualitative approach with a participatory mentoring model consisting of three stages: financial digitalization socialization, technical training on application usage, and intensive mentoring in implementing digital financial recording. Data were collected through observation, informal interviews, and documentation during the program. The results indicate an improvement in participants’ understanding of systematic financial recording and enhanced skills in using digital tools to record business transactions. The partners were also able to prepare periodic income statements and cash flow reports and began separating personal and business finances. The digitalization of financial recording improved data accuracy, reporting efficiency, and transparency in business financial management.